산화알루미늄 섬유와 니켈분말 후처리공정에서 입자의 노출특성 - 김종범; 김경환; 류성희; 윤성택; 배귀남 (한국산업보건학회, 2016)
Objectives: Nanomaterials have been used in various fields. As use of nanoproducts is increasing, workers dealing with nanomaterials are also gradually increasing. Exposure assessments for nanomaterials have been carried out for protection of worker’s health in workplace. Exposure studies were mainly focused on manufacturing processes, but these studies on after-treatment processes such as refinement, weighing, and packing were insufficient. So, we investigated exposure characteristics of particles during after-treatment processes of Al2O3 fibers and Ni powders. Methods: Mass-production of Ni powder process was carried out in enclosed capture-type canopy hood. In a developing stage, Al2O3 was handled with a local ventilation unit. Exposure characteristics of particles were investigated for Al2O3 fiber and Ni powder processes during the periods of 10:00 to 16:00, 20 May 2014 and 13:00 to 16:00, 21 May 2014, respectively. Three real-time aerosol instruments were utilized in exposure assessment. A scanning mobility particle sizer(SMPS, nanoscan, model 3910, TSI) and an optical particle counter(OPC, portable aerosol spectrometer, model 1.109, Grimm) were used to determine the particle size distribution in the size range of 10？420 nm and 0.25？32 μm, respectively. In addition, a nanoparticle aerosol monitor(NAM, model 9000, TSI) was used to measure lung-deposited nanoparticle surface area. Membrane filters(isopore membrane filter, pore size of 100 nm) were also used for air sampling for the FE-SEM(model S-5000H, Hitachi) analysis using a personal sampling pump(model GilAir Plus by 2.5 L/min, Gilian). Conclusions: For Ni powder after-treatment process, only 27% increase in particle concentration was found during the process. However, for Al2O3 fiber after-treatment process, significant exposure(1.56-3.34 times) was observed during the process.